The Inhibition Effect of Ampicillin on Corrosion of Pure Aluminium in 3.5% NaCl Aqueous Solution. - Hameed, Samar T; Salman, Taghried A; Al-Saidi, Shatha F (Al-Nahrain Journal of Science, 2018)
The Inhibition of the corrosion of pure aluminium in 3.5% NaCl aqueous solution using ampicillin has been studied using potentiodynamic polarization and scanning electron microscopy (SEM) techniques. It was found that the ampicillin effectively reduces the aluminium corrosion in the saline solution. Inhibition efficiency (%IE) is increased as the inhibitor concentration increases; on the other hand, (%IE) is decreased when the temperature increases. The adsorption of inhibitor on metal surface was spontaneous and follows Langmuir adsorption isotherm. Quantum mechanical has been accomplished using B3LYP/6-31G basis set method to ascertain any correlation between the inhibitive effect and molecular structure of ampicillin.